Intraperiod Income Tax Allocation with Differential Rates. - Kiger, Jack E.; Wilcox, James B.; Williams, Jan R. (The Accounting Review, 1977)
Abstract ABSTRACT: Present financial statement disclosure standards require that certain items be separately classified in the financial statements and presented net of their applicable income tax. Examples of such items are the cumulative effect of a change in accounting principle, an extraordinary item and a gain or loss resulting from the disposal of a segment of a business. The determination of the income tax effect of such items is complicated when there are differential tax rates and multiple items which must be specially classified. The purpose of this paper is to demonstrate this process and to discuss the complexities that arise when the specially classified items include offsetting gains and losses.